Integrating Islamic Criminal Law and International Human Rights Law in Counter-Terrorism Efforts: A Critical Analysis - Suleiman, Nashwan Mohammed; Armoosh, Saud Suwaid; Salih, Rami; Al-Obaidi, Salman Husain; Chornomordenko, Dmytro (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
The article examines the effectiveness of counter-terrorism strategies in aligning with international human rights law (IHRL) and Islamic criminal law (ICL). The rise in global terrorism has led governments to implement stringent counter-terrorism measures, often resulting in conflicts between maintaining national security and upholding human rights and Islamic legal principles. Through a comprehensive review of international legal instruments, Islamic legal texts, case law, and national counter-terrorism policies, a comparative analysis was conducted to assess the extent of conformity between state measures and international human rights standards, alongside the principles of ICL. The findings reveal that while many countries attempt to incorporate human rights protections and Islamic values into their counter-terrorism frameworks, these efforts are often undermined by practices such as prolonged detention without trial, torture, and restrictions on freedom of expression and association. Furthermore, inconsistencies in the interpretation and application of ICL across jurisdictions were observed. The study concludes that states must balance the imperative of ensuring national security with their obligations under international human rights law and Islamic criminal law. Although it is possible to formulate effective counter-terrorism strategies within these frameworks, governments must remain vigilant and committed to upholding both security and human rights.